Pelatihan Impedance Matching Circuits dengan Aplikasi Smith Chart dari Playstore Android - Imelda Uli Vistalina Simanjuntak; Lukman Medriavin Silalahi; Freddy Artadima Silaban; Setiyo Budiyanto Budiyanto; Agus Dendi Rochendi (Asosiasi Dosen Pengabdian kepada Masyarakat Indonesia, 2021)
Industry demand for skilled human resources presents a challenge for every school graduate to conduct various competency and skills training. So, the solution to meet industry challenges is a training on the application of science and technology for the community entitled